Level of Knowledge of Boarding School Students in First Aid Management of Syncope - Amni, Rahmalia; Fikriyanti, Fikriyanti; Aklima, Aklima (CV. Global Health Science Group, 2024)
Syncope is a condition that requires proper and fast first aid. Boarding school students stay twenty-four hours in a dormitory and students often experience syncope for various causes, so boarding school students need independent first aid skills for syncope. Objective: This study aimed to identify the level of knowledge of boarding school students in providing first aid for syncope cases. Method: This research uses quantitative research methods with a cross-sectional descriptive design. The sampling technique in this research was total sampling, with a sample size of 110 respondents. Data collection used a modified questionnaire, and the validity has been tested at r > 0.1857 and the Cronbach alpha value is 0.89. Data analysis was conducted descriptively using a computerized program. Results: Comprehensive research shows that 10.9% of boarding school students have high knowledge of first aid in cases of syncope, 71.8% have medium knowledge, and 17.3% have low knowledge. Conclusions: This research shows that the majority of boarding school students' knowledge level in first aid for syncope cases is still in the sufficient and poor categories.